Authenticity and the authentication of heritage: dialogical perceptiveness. Issue 5 (2nd November 2019) - Chhabra, Deepak
ABSTRACT: The dialogue on authenticity continues to evolve across different temporalities and disciplines. This editorial for the special issue summarizes contemporary progress made by scholars of heritage tourism and shares innovative corridors for deep deliberations. A broad spectrum of provocative ideas are touched upon, ranging from host–guest authentication and intangible heritage to knowledge transfer processes, authenticating heritage in fairytale settings, authenticity and anxiety in the smell of death and life, understanding the boundaries of authenticity, nostalgia, sustainability, marketing, destination competitiveness, and examining affective connotations of authenticity. Discursive insights are offered on how different authenticities are legitimized and critically deconstructed and re-constructed again in the authentication process, to underline the existence of power and authority interventions. Inspiring/innovative pathways, for future research, are also recommended.